COVID-19 and British Columbia’s volunteer search and rescue workers: risk recognition and risk mitigation - David Birnbaum; Vienna C. Lam; Farinaz Havaei; Gail S. Anderson (Antimicrobial Stewardship & Healthcare Epidemiology, 2023)
Abstract